The effect of recitation Al- A’ mash on directing the Qur’anic text of Al- Zamakhshari in Al- kashaf: An analytical study - Ali, Husam Gassan (Journal of Humanities & Social Sciences, 2021)
The title of the study relates to what’s been known of AL A’MASH in his Quran recitation, contrary to the recitation of the public, as contained in (Al KASHAF) of AL Zamakhshari, revealing with no doubt the effect of his recitation in guiding the Quranic text, as shown by AL Zamakhshari and other Arab scholars, so they split into four opinions: those who said it’s allowed, those who repelled it, those who said it’s a weak recitation and those who deemed it irregular. For the study of the recitation showed that some parts were out of the known measured language rules of Arabic, and other parts were out of the known aural rules, while a third party found it to be uncommon. Therefore, the study aims to present and clarify, try investigating as much information as possible.